2011
DOI: 10.1074/jbc.m111.250928
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Amelogenin Protein Nanospheres

Abstract: Amelogenin self-assembles to form an extracellular protein matrix, which serves as a template for the continuously growing enamel apatite crystals. is involved in protein-protein interaction. The truncated rP148 formed similar but smaller oligomers, suggesting that the C terminus is not critical for amelogenin oligomerization. We propose a model for nanosphere formation via oligomers, and we predict that nanospheres will break up to form oligomers in mildly acidic environments via histidine protonation. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 51 publications
(40 reference statements)
6
76
1
1
Order By: Relevance
“…Site-directed mutagenesis was carried out on the DNA template of full-length porcine amelogenin rP172 to generate four mutant proteins, specifically rP172(W25Y,W45Y), rP172[(W25Y,W45Y,W161Y),(F112W)], rP172(W25Y,W161Y), and rP172(W45Y,W161Y), and using Quick Change mutagenesis (Agilent Technologies) as described elsewhere [15,17]. These mutants were designed such that each has only one tryptophan in its entire sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis was carried out on the DNA template of full-length porcine amelogenin rP172 to generate four mutant proteins, specifically rP172(W25Y,W45Y), rP172[(W25Y,W45Y,W161Y),(F112W)], rP172(W25Y,W161Y), and rP172(W45Y,W161Y), and using Quick Change mutagenesis (Agilent Technologies) as described elsewhere [15,17]. These mutants were designed such that each has only one tryptophan in its entire sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Four different amelogenin mutants containing only a single tryptophan (Trp161, Trp112, Trp45 or Trp25) were used for fluorescence analysis [17]. By creating these single-tryptophan amelogenins, which behaved in the same way as the wild type, we were able to identify phospholipid-interacting domains.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent CD analysis has revealed that while oligomer formation accompanies conformational changes in amelogenin, little structural change occurs as a result of nanosphere formation. 54 In their NMR studies, Lu et al . 55 reported a lack of conformational changes in amelogenin nanospheres during gel formation.…”
Section: Amelogenin and Its Targetsmentioning
confidence: 99%
“…We have reported that amelogenin oligomer formation in vitro is mediated by N-terminal protein-protein interactions and assembly, while nanosphere formation is mainly regulated by hydrophobic interactions via the histidine-rich central portion. 54 The question is whether the amelogenin oligomers (R H = 7.5 nm) are the functional entities in enamel formation and that the nanospheres (R H = 14nm) are simply the result of aggregation of oligomers. Particles of 15–20 nm in diameter detected by TEM are the oligomeric structures that were detected in between enamel crystallites.…”
Section: Amelogenin and Its Targetsmentioning
confidence: 99%
See 1 more Smart Citation